Management engineering : a guide to best practices for industrial engineering in health care - Larson, Jean Ann (CRC Press, Taylor & Francis Group, 2014)
"The healthcare industry continues to offer process engineers ample opportunities to streamline processes. Increasing costs along with higher utilization of resources make the role of process improvement even more important. This book provides an overview of the unique and invaluable roles that process improvement specialists play in healthcare organizations. It describes, through the use of case studies, tried and true techniques. It also provides practical examples of the application of those techniques. The books explains how best to utilize the unique skills of management engineers in a healthcare setting"--Provided by publisher.
Keywords: zdravotnický management -- Spojené státy americké; procesní management -- Spojené státy americké; health service management -- United States; process management -- United States; příručky; handbooks and manuals